2017
DOI: 10.1016/j.bjorl.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous malformation of the external ear: a clinical assessment with a scoping review of the literature

Abstract: Auricular arteriovenous malformation is a rarely encountered disease, but should be suspected if a patient presents with a swollen ear and pulsatile tinnitus. Appropriate imaging is essential for diagnosis and evaluation of the extent of disease. As embolization affords only relatively poor control, total surgical removal of the vascular mass is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
1
19
0
1
Order By: Relevance
“…Ear AVMs have low incidence, and few reports in the literature have defined guidelines for its management . Treatment should be focused on the extent of resection.…”
Section: Discussionmentioning
confidence: 99%
“…Ear AVMs have low incidence, and few reports in the literature have defined guidelines for its management . Treatment should be focused on the extent of resection.…”
Section: Discussionmentioning
confidence: 99%
“…This makes clinical diagnosis quite straightforward, although this is not always the case as reports of initial misdiagnosis have been noted. This was the case in our patient who was initially diagnosed and managed for Auricular Haemangioma at the source of referral [3]. Diagnostic and interventional radiological procedures make management of AVM less difficult.…”
Section: Discussionmentioning
confidence: 62%
“…It has been reported that 50% of the head and neck AVMs affect the oral and maxillofacial region [4 , 7] . In a retrospective review of 81 patients with an AVM of the head and neck, Kim et al reported that cheek was the most common site (31%) followed by ear (16%) [11] . Race or sex predilection has not been demonstrated, [5 , 12] although Spreafico et al have reported a male:female ratio of 1:1.5 [13] .…”
Section: Epidemiologymentioning
confidence: 99%